Poisoning by Eating of Toxic Wild Plant - Huy , Ba Le; Xuan, Hoan Nguyen; Tan , Phong Nguyen; Minh, Thanh Le (Food Toxicology: Theory, Practice and Resolve in Vietnam, 2022)
The basic content of chapter 13 is to state the cause of human poisoning by eating poisonous plants and mushrooms. Our country is diverse in species of plants and animals, beneficial and harmful plants and animals always exist in parallel with each other to balance the ecosystem. For poisonous plants in particular, it has different advantages and disadvantages. For example, some plants can be used as medicine in low doses, but if not careful, it becomes an extremely toxic substance. can be dangerous to human life. In order to prevent the harmful effects of poisonous plants to people living near mountainous areas, deep-lying areas, dense forests, etc., the government needs to widely propagate the harmful effects of plants. on places frequented by the public and in all mass media.